PENGARUH TRANSAKSI LEASING TERHADAP PERHITUNGAN PAJAK PENGHASILAN BADAN PADA PT RODES CHEMINDO - Stefvy Stefvy; Robin Robin (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this research is to know implementation of financing leasing according to income tax provision and its impact to entity’s tax expense at PT Rodes Chemindo. Types of this research is in form of descriptive research with case study in PT Rodes Chemindo and the research object is analyzing finance leasing transaction in PT Rodes Chemindo and analyzing the impact of finance leasing transaction to entity’s income tax. Data which is collected is secondary data include the presentation of financial statement, income tax expense calculation, finance leasing transaction, depreciation calculation, accounting of finance leasing transaction and other information which is related with this research. The research result shows that implementation of finance leasing has impact in increasing entity income tax in PT Rodes Chemindo. Fiscal expense in the company is not in accordance with income tax provision because the company recognizes the depreciation expense and interest expense of leased fixed asset. Income tax payable after implementation of income tax provision in year 2020 is Rp 78,357,833.00 with result that there is increasing of income tax payable year 2020 in Rp 8,264,960.00. Positive fiscal correction should be done for interest expense in Rp 67,160,860.00 and depreciation expense in Rp 99,218,750.00. The company can recognize leasing installment payment in Rp 128,811,570.00 as deductible expense in year 2020. The company should classify the leased fixed asset as leasing transaction based on income tax provision in calculating the income tax payable. The company records the finance leasing transaction as fixed asset. Payment of leasing is recorded as deduction of leasing liabilities. The company also records the depreciation expense of leased fixed asset and interest expense. The company has properly classified the leased fixed asset as leasing transaction. Income tax expense in the company is Rp 626,371,240.00 and income tax expense after implementation of income tax provision is Rp 634,636,200.00.